A Thom isotopy theorem for nonproper semialgebraic maps - Dias, Luis Renato Gonçalves; Ramos, Giovanny Barrera (Topological Methods in Nonlinear Analysis, 2026)
We prove a version of the Thom isotopy theorem for nonproper semialgebraic maps fX→ R^m, where X R^n is a semialgebraic set and f is the restriction to X of a smooth semialgebraic map FR^n→ R^m.